Phosphate and potash solubilizing bacteria from Moroccan phosphate mine showing antagonism to bacterial canker agent and inducing effective tomato growth promotion - Bouizgarne, B.; Bakki, M.; Boutasknit, A.; Banane, B.; El Ouarrat, H.; Ait El Maalem, S.; Amenzou, A.; Ghousmi, A.; Meddich, A. (Frontiers in Plant Science, 2023)
Isolation of phosphate solubilizing bacteria from Moroccan phosphate mine led to the selection of two isolates Bg22c and Bg32c showing high solubilization potential. Phosphate solubilization was performed. The two isolates were also tested for other in vitro PGPR effects: in addition to phosphates, they were able to solubilize insoluble potassium and zinc forms (P, K, Z solubilizers) and to produce indole-acetic acid (IAA). Mechanisms of solubilization involved organic acids production as demonstrated by HPLC. In vitro, the isolate Bg22c was able to antagonize the phytopathogen Clavibacter michiganensis subsp. michiganensis causal agent of tomato bacterial canker. Phenotypic and molecular identification by 16S rDNA sequencing demonstrated delineation of Bg32c and Bg15d as member of the genus Pseudomonas while Bg22c as member of the genus Serratia. The two isolates Bg22c and Bg32c were further tested either alone or in a consortium and compared to the non P, K, Z-solubilizing bacterium Bg15d, for their efficacy to promote tomato growth and yield and compared to treatment with a conventional NPK fertilizer. Under greenhouse conditions, strain Bg32c remarkably improved the growth of whole plant height, root length, shoot and root dry weight, number of leaves and fruits, as well as fruit fresh weight. This strain also induced stomatal conductance enhancement. The strains also improved total soluble phenolic compounds, total sugars, protein and phosphorus contents compared to the negative control. All increases were more pronounced in plants inoculation with Pseudomonas strain Bg32c in comparison with control and non PKZ solubilizing bacterium Bg15d. The strain Bg32c could be considered a potential candidate for formulation of a biofertilizer in order to improve tomato growth.